Hegemony and Transformation: A Comprehensive Analysis of Gender Issues in the Global Dynamics of the 21st Century - Laksmi, Putu Putri Dena; Lasmawan, I Wayan; Parmiti, Desak Putu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Gender inequality remains one of the most pressing challenges on the global development agenda. Although significant progress has been achieved through the MDGs and SDGs, the gap between men and women in economic access, political representation, and personal security remains very wide. This study aims to explore the sociological roots of gender inequality, its impact on the global economy, and how the currents of globalization and digitalization create both new opportunities and threats to gender justice. The method used in this study is a comprehensive analysis through an in-depth literature review of patriarchal structures, intersectionality theory, and the dynamics of gender issues in the 21st century. The analysis covers the mechanisms of perpetuating patriarchy through the institutions of family, education, and religion, as well as its manifestations in the capitalist economy and digital space. The results show that patriarchal hegemony remains a structure that is difficult to dismantle and is transforming into more complex forms in the digital era, such as technology-mediated gender-based violence. The gender wage gap and unpaid care work continue to hinder global economic potential, while women's representation in strategic decision-making remains far from targets. Intersectionality theory emphasizes that the discrimination experienced by women overlaps with issues of race, class, and colonialism, thus requiring non-monolithic solutions. This study concludes that gender transformation is not merely a moral issue but a prerequisite for the progress of civilization, demanding legal reform, inclusive education, and cross-national commitment to deconstruct oppressive hegemonic structures.